Immunosuppressive cells in oncolytic virotherapy for glioma: challenges and solutions - Liu, Junfeng; Piranlioglu, Raziye; Ye, Fei; Shu, Kai; Lei, Ting; Nakashima, Hiroshi (Frontiers in Cellular and Infection Microbiology, 2023)
The aggressive form of glioma, glioblastoma, is referred to as a myeloid disease of the brain, in which lineage cells dominate most of the tumor-infiltrating immune population in the tumor microenvironment. These myeloid cells, including tumor-associated macrophages and microglia (TAM) and myeloid-derived suppressor cells (MDSCs), play a pivotal immunosuppressive role in the tumor microenvironment and contribute to tumor progression. Oncolytic viruses (OVs) are self-amplifying cytotoxic drugs that accompany local anti-tumor immune responses. OV actions can play a role in suppressing immunosuppressive myeloid cells and prompt the recruitment of tumor-infiltrating T lymphocytes (TILs) to the tumor site, triggering an adaptive immune response against tumors. However, it is still underway to understand how the action of OV therapy impacts the tumor-resident myeloid population and consequent reactions. This review mainly overviews how TAM and MDSC react to different types of OVs, and combination therapeutics that target the myeloid population to anti-tumor favored immune responses in the glioma microenvironment.